FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEKAMBUHAN GASTRITIS - Nuruniyah, Nuruniyah; Zamli, Zamli; Ernita, Ernita; Rosyida, Muslihatin Khuril; Menga, Maria Kurni (Ensiklopedia of Journal, 2024)
Based on data from the Bengkulu City Health Office in 2020, gastritis ranked sixth out of the ten largest diseases, with a total of 13,471 cases. The highest incidence of gastritis is in the Nusa Indah Health Center working area with 620 cases. The highest incidence of gastritis in 2020 was 98 patients. Nusa Indah Village, most people do not pay attention to healthy living habits because of their busy daily lives. The purpose of the study was to determine the factors associated with gastritis recurrence. The research method uses a cross sectional research design. The population in the study amounted to 98 people with a sample size of 49 respondents with random sampling technique. Data analysis used univariate and bivariate. The results of the study with statistical tests showed the value of stress p value: 0.000, diet p value 0.006, and the use of drugs p value 0.010. It is recommended for the health center to consider the importance of health counseling and management to reduce the recurrence of gastritis in the form of factors that trigger gastritis recurrence so that visits with complaints of gastritis recurrence are reduced.Keywords: Gastritis, Stress, Diet, Medication Use